Deactivation mechanism of SO2 on Cu/SAPO-34 NH3-SCR catalysts: structure and active Cu2+. Issue 3 (22nd December 2014) - Shen, Meiqing; Wen, Huaiyou; Hao, Teng; Yu, Tie; Fan, Dequan; Wang, Jun; Li, Wei; Wang, Jianqiang
Abstract : The deactivation mechanism of structure and active site for Cu/SAPO-34 catalysts by SO2 poisoning has been investigated using a range of analytical techniques. Abstract : The deactivation mechanism of Cu/SAPO-34 ammonia selective catalytic reduction catalysts (NH3 -SCR) by SO2 poisoning has been systematically investigated using a range of analytical techniques in order to study the influence on both the zeolitic framework and the active Cu 2+ ions. The different sulfate samples were obtained by SO2 poisoning over Cu/SAPO-34 NH3 -SCR catalysts as a function of time and concentration in the feed. The obtained results reveal that the SO2 poisoning could seriously decrease NO conversion during the whole temperature range (100–500 °C). The XRF results shows that there is almost no sulfur existing on the SAPO-34 support. The ex situ DRIFTS and BET results reveal that SO2 poisoning has a less-pronounced effect on its framework structure. The TPR and EPR results demonstrate that SO2 poisoning has a significant influence on the coordination environment and the content of the active isolated Cu 2+ species. The kinetic results demonstrate that the SO2 poisoning does not influence the apparent activation energy ( E a ) of the NH3 -SCR reaction over Cu/SAPO-34 catalysts. The decline of the NH3 -SCR activity is due to the reduction of the number of isolated Cu 2+ ions.